Knowledge and Attitude towards Prevention and Management of Hypertension in Jatinangor Sub-district - Kartika Malahayati; Rudi Supriyadi; Herri S. Sastramihardja (Althea Medical Journal, 2016)
Background: There is an increase in prevalence of hypertension all over the world as well as Indonesia. Hypertension affects almost all body organs and systems. Hypertension prevention and management are influenced by knowledge and attitude towards the disease. The aim of this study was to assess knowledge and attitude towards prevention and management of hypertension.Methods: This was a descriptive study with cross–sectional approach conducted in Jatinangor sub-district in 2013. Sample sizes were determined based on proportion of the case in population and precision estimates (95% confidence intervals). One hundred twenty respondents aged 18–60 year-old were selected from population using stratified random sampling method. Hypertensions knowledge and attitude were assessed using validated questioner as the scale measurement. Frequency of knowledge level was presented as three ordinal categories; good, moderate, and poor. Attitude of hypertension was presented as frequency in two categories; relatively positive and relatively negative.Results: Out of 120 respondents administered the questioner, 42.50% had good knowledge; 41.67% had moderate knowledge; 15.83% had poor knowledge related to hypertension prevention and 21.67% had good knowledge; 19.17% had moderate knowledge; 59.17% had poor knowledge related to management of hypertension. Hypertension attitude of respondents were 60.83% relatively positive in topics of hypertension prevention and 39.17% in topics of hypertension management.Conclusions: Respondents are knowledgeable about hypertension prevention but are less knowledgeable about its management. Respondents have relatively positive attitudes towards hypertension prevention. In the other hand, respondents have more relatively negative attitudes towards its management. [AMJ.2016;3(2):222–9]DOI: 10.15850/amj.v3n2.801